The Role of Leaders in Prince Saud University in Activating Self-directed Training - Al-Ohali, Hanan Hamad; Al Mazroua, Shatha Mazroa (The Arab Journal of Administration, 2024)
The research aimed to study the role of leaders in Prince Saud University in activating the training curriculum, the used research sample is female members of the administrative staff of Prince Saud University in Riyadh, the members are (331). The used research tool is questionnaire. The study concluded with several results, the most important of which are: The degree of (the role of leaders in activating self-directed training) was neutral, with an arithmetic mean of all dimensions reaching (2.12). The study sample also agreed that there are obstacles to self-training with a degree that is in agreement with an arithmetic average for all axes of (2,44). There are also statistically significant differences between the averages of the study sample responses about the role of the direct manager in activating self-directed training due to the difference in scientific qualification in favor of (secondary). There are also statistically significant differences between those who hold a scientific qualification (university) and those who hold an academic qualification (postgraduate studies). There are no statistically significant differences between the averages of the study sample responses about obstacles to self-directed training due to the difference in academic qualification. There are no statistically significant differences between the averages of the study sample responses on all study axes due to the difference of the employer. The study recommends the necessity of material and moral encouragement for employees when they practice self-training, counting the courses resulting from self-training in promotions, and avoiding routine tasks in order to push the employee towards self-directed training.